Role of Fe2+-dependent Reaction in Biodecolorization of Methyl Orange by Brown-rot Fungus Fomitopsis pinicola - Adi Setyo Purnomo; Asranudin; Nela Rachmawati; Hamdan Dwi Rizqi; Refdinal Nawfa; Surya Rosa Putra (Bogor Agricultural University, Indonesia, 2022)
The involvement of Fenton reaction on biodegradation of methyl orange (MO) by brown-rot fungus Fomitopsis pinicola was investigated based on Fe2+-dependent reaction. The degradation of MO (final concentration 75 mg/L) was performed in mineral salt media with and without Fe2+ with incubation period at 0, 7, 14, 21, and 28 days. Degradation analysis was performed using UV-Vis Spectrophotometer and LC-TOF/MS. F. pinicola decolorized MO in a medium containing Fe2+ and a medium that lacked the mineral, at percentages of 89.47% and 80.08%, respectively. The optimum decolorization occurred after 28 days of incubation with the fungus on the presence of Fe2+, indicated that the presence of Fe2+ enhanced MO degradation with assumed to correlate with Fenton reaction. Two metabolites were detected through the LC-TOF/MS analysis, namely 4-(2-(4-(dimethyliminio)-2-hydroxycyclohexa-2,5-dien-1-ylidene) hydrazinyl) phenolate (m/z 258, RT: 1.28 min, compound 1) and 4-(2-(4-(dimethyliminio) cyclohexa-2,5-dien-1-ylidene) hydrazinyl) benzenesulfonate (m/z 391, RT: 2.70 min, compound 2). Compound 1 was a transformation product of hydroxylation and methylation, compound 2 was a product of dehydroxylation and desulfonation. This study indicated that the transformation of the metabolite structures was involved hydroxyl radical (OH.) and enzymatic mechanisms, which involved Fe2+-dependent reaction.